Chinese exports to Central Asia after Russia's invasion of Ukraine - Henna Hurskainen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
This paper looks at the development of Chinese exports to Central Asian countries after Russia's invasion of Ukraine in February 2022. The analysis, which relies on export data from China to Asian countries at a general product level, shows that China's exports to Central Asia have significantly increased since the start of the war. In particular, exports to Kazakhstan, Uzbekistan, and Kyrgyzstan have increased significantly. The analysis focuses on exports in Harmonized System (HS) categories 84, 85, 87, and 90. Many of the products sanctioned by the West in trade with Russia belong to these categories, but the categories also include many non-sanctioned products. Although the value of China's exports to Central Asia is still smaller than direct trade with Russia, China's exports - especially to Kyrgyzstan - have seen dramatic increases in the HS 84, 85, 87, and 90 categories. Along with the export growth from China to Central Asia, exports in these categories from Central Asia to Russia have also increased significantly.
urn:nbn:fi-fe2024091371049
Keywords: 330; China; Central Asia; Russia; exports